Subtitusi Tepung Maggot (Hermetia illunces) Dengan Tepung Ikan Untuk Pertumbuhan dan Kelangsungan Hidup Benih Ikan Mas Koi (Cyprinus Carpio Linneaus) - Ekowanto Doholio; Rully Tuiyo; Arafik Lamadi (Research Review: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to discover the effect of subtitution of maggot flour (Hermetua illunces) with fish flour as animal feed for the growth and survival of Cauliflower Gold Fish (Cyprinus Carpio Linneaus). Moreover, it is also to discover the best percentage of maggot flour as an alternative ingredient to subtitute the fish flour to create impacts on the growth and survival  of Cauliflowe Golf Fish (Cyprinus Carpio Linneaus). In regards to that, thus study was caried put for 35 days during  September-November 2022 at the Fish Seed Center (BBI) Gorontalo City. This using 4 treatments with 3 repetitions: Threatment A (Control) 0% Maggot Flour, Threatment B 10% Maggot Flour, Threatment C 20% Maggot Flour, Threatment D 30% Maggot Flour.bThe result showed that maggot flour subtitution did not have significant impact on the growth and survival of Cauliflower Gold Fish (Cyprinus Carpio Linnaeus).